The Impact of Country Level Factors of the Western Balkans on the Choice of Offshoring Location - Krejčířová, Kristýna; Semenenko, Vadim; Procházka, Petr; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This bachelor’s thesis examines how country-level factors in the Western Balkan region influence firms’ decisions when choosing an offshoring location. The aim of the thesis is to assess which aspects most strongly shape the attractiveness of individual countries and whether the region represents a suitable alternative to traditional offshoring destinations. The theoretical section focuses on the development of offshoring, firms’ motivations, and current trends, including nearshoring and reshoring. The practical section uses a PESTLE analysis to compare eight countries - Albania, Bosnia and Herzegovina, Croatia, Hungary, Montenegro, North Macedonia, Serbia, and Slovenia - based on available macroeconomic and institutional indicators. The analysis reveals key differences among the countries, particularly in political stability, unemployment, and the quality of the legal environment. The empirical section is based on qualitative analysis and draws on four structured interviews with managers from companies operating in various industries that already offshore to the region. The findings show that the key factors influencing decisions include low labor costs, the availability of a skilled workforce, and geographic proximity to European markets. The main barriers include political uncertainty and administrative complexity. In conclusion, the results indicate that the Western Balkans has growing potential as a nearshoring destination. However, for the region to fully capitalize on its opportunities, it needs, among other things, to strengthen political stability, invest in human capital, improve infrastructure, and implement effective measures to retain a skilled workforce in the region. The thesis, therefore, offers recommendations for both economic policymakers and companies considering relocating their activities to this region.
Vedoucí práce: Vadim Semenenko
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses